Proceedings of the XXI International Mineral Processing Congress - Massacci, Paolo (Developments in mineral processing, 2000)
These three volumes (Golden Nuggets) present the latest knowledge in the science and technology of mineral processing and new industry applications, related to the following topics: mineral and material characterization and liberation, comminution, classification and agglomeration, hydro and biohydrometallurgy, physical separation processing, flotation, and process simulation and control. Due to the increasing application of mineral processing techniques in waste treatment, recycling and soil remediation have received special attention. The three volumes present a selected collection of peer-reviewed papers devoted both to the theory of mineral processing (Volumes A and B) and to process design and plant application (Volume C).